2022
DOI: 10.21203/rs.3.rs-1352086/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Omnitrophota encompasses diverse and hyperactive nanobacteria: Potential metabolisms and host-dependent lifestyles

Abstract: Candidate bacterial phylum Omnitrophota has never been grown in axenic culture and is poorly understood. Here, we combined analysis of 421 Omnitrophota genomes representing six classes and 276 species and show that they are prevalent in water, sediments, and soils globally. Fluorescence-activated cell sorting and differential size filtration showed ultra-small (~0.2 μm) cells to be common across the phylum. Reduced genomes in all six classes maintained major biosynthetic and energy conservation pathways, parti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 98 publications
(148 reference statements)
1
6
0
Order By: Relevance
“…Putative fermentation and presence of genes for the Wood‐Ljungdahl pathway are highly abundant in Omnitrophota MAGs (Figure 5). The prevalence of the Wood‐Ljungdahl pathway in Omnitrophota genomes has been noted in other studies (Momper, Jungbluth, et al, 2017; Perez‐Molphe‐Montoya et al, 2022; Seymour, 2021; Seymour et al, 2023) and seems ubiquitous among the numerous clades of this candidate phylum, indicating an anaerobic and potentially mixotrophic lifestyle. Finally, analysis of D3_22, a high quality Eisenbacteria MAG, reveals that members of this candidate phylum may have highly diverse metabolic capabilities in DeMMO fluids, including nitrogen, sulfur, metal and oxygen transformation.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Putative fermentation and presence of genes for the Wood‐Ljungdahl pathway are highly abundant in Omnitrophota MAGs (Figure 5). The prevalence of the Wood‐Ljungdahl pathway in Omnitrophota genomes has been noted in other studies (Momper, Jungbluth, et al, 2017; Perez‐Molphe‐Montoya et al, 2022; Seymour, 2021; Seymour et al, 2023) and seems ubiquitous among the numerous clades of this candidate phylum, indicating an anaerobic and potentially mixotrophic lifestyle. Finally, analysis of D3_22, a high quality Eisenbacteria MAG, reveals that members of this candidate phylum may have highly diverse metabolic capabilities in DeMMO fluids, including nitrogen, sulfur, metal and oxygen transformation.…”
Section: Discussionsupporting
confidence: 73%
“…Members of the phylum Omnitrophota are particularly well represented in our dataset with MAGs originating from across DeMMO sites. The phylum was originally dubbed ‘Omnitrophica’ in 2013 (Rinke et al, 2013) and has received much attention in recent years, as they are a widespread and abundant candidate phylum in global natural environments such as sediment, non‐saline ground and surface water, and soils (Perez‐Molphe‐Montoya et al, 2022; Seymour, 2021; Seymour et al, 2023; Williams et al, 2022). Recent studies have posited that most Omnitrophota are ultra‐small nanobacteria (cell size <0.2 μm) and that they lead a symbiotic lifestyle (Seymour, 2021; Seymour et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study reported that Leptospirae, one of the taxa not found after the incubation, had difficulties multiplying following a microcosm experiment (Casanovas‐Massana et al., 2018). Another taxon, Omnitrophia, is known for its host‐dependent lifestyle (Seymour et al., 2022). It is likely that the altered environment during our incubation removed such hosts and lessened their survivability.…”
Section: Discussionmentioning
confidence: 99%
“…The potential tendency for introduced microbial cells to be retained in porous/fractured media, on the other hand, highlights the abundant indigenous microbes that did transport out of the aquifer. A notable category of the produced-fluid members is, interestingly, those with documented ultrasmall body size, for example, members of the phyla Patescibacteria (also known as the Candidate Phyla Radiation or CPR) and Omnitrophicaeota (also known as Omnitrophota, Omnitrophica or OP3) [67,68], both of which still lack culturable representatives, yet were found to be prevalent in oligotrophic groundwater environments worldwide in high abundance [25,[67][68][69]. Among the 50 samples in this study, members of the Patescibacteria and Omnitrophicaeota phyla were prevalent and constituted up to 39.3% and 16.1% of the produced communities, respectively.…”
Section: Retention Of Injectate Microbes In Contrast With Mobility Of...mentioning
confidence: 99%